A Review on Recent Advances in Silk Sericin, Extraction, Properties, Applications and Future Perspectives - , Michael Thanga; Lalhmangaihzuali, Jugabrat Sarma; Zonunmawii, Aroos Rauf Rafiqu, Mohammad Rafiq Bhat (Archives of Current Research International, 2025)
Silk sericin, traditionally considered a waste by-product of the silk industry has recently gained attention as a multifunctional biomaterial with applications across biomedical, cosmetic, nutraceutical and environmental sectors. Its unique amino acid composition and bioactive properties including antioxidant, antimicrobial, anti-inflammatory and moisturizing effects make it a promising candidate for next-generation products. The aim of this review is to consolidate recent advances in the extraction methods, structural properties and diverse applications of silk sericin, while highlighting its translational potential from laboratory research to industrial implementation. Special emphasis is given to sustainable recovery approaches and its role in the circular bioeconomy aligning with global priorities in green chemistry and waste valorization. In addition, the review identifies research gaps such as standardization of large-scale extraction, regulatory approval challenges and the need for long-term safety studies. By addressing these gaps future research can accelerate the transition of sericin from a discarded effluent into a high value biomaterial that bridges sericulture with modern healthcare, industry and sustainability.